The Coca Connection:: Conflict and Drugs in Colombia and Peru - Felbab-Brown, Vanda (Journal of Conflict Studies)

(untitled) (The University of New Brunswick, 2005)
ABSTRACT Analysis of the connection between the narcotics economy and insurgent movements in Peru and Colombia shows that access by belligerents to the illicit economy greatly strengthens the insurgent movements. However, the belligerents' gains are not simply in the form of financial assets and enhanced military capabilities as frequently assumed, but are also in the form of expanded strategic and tactical options and, crucially, improved relations with local popu lations. Premised on the desire to reduce the physical capabilities of the belligerents, government attempts to defeat the insurgency through crop eradication not only fails to significantly reduce the belligerents' capabilities, but are also often counterproductive. Crop eradication only strengthens the bond between the belligerents and the local population, and deprives the government of vital intelligence on the belligerents.